Hope and Folly : The United States and UNESCO, 1945-1985 - Preston, William, 1924- (Book collections on Project MUSE., 1989)
Hope and Folly was first published in 1989. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. Created in a burst of idealism after World War II, the United Nations Educational, Scientific, and Cultural Organization (UNESCO) existed for forty years in a state of troubled yet often successful collaboration with one of its founders and benefactors, the United States. In 1980, UNESCO adopted the report of a commission that surveyed and criticized the dominanc.